Uma contribuição ao processo de ensino e aprendizagem dos alunos de educação à distância da UFERSA - Nascimento, Ana Beatriz Morais Lima do (Universidade Federal Rural do Semi-Árido, 2017)
The search for professional qualification and technological advances are inducing changes in the educational environment. In this context, the institutions aim to use the method of teaching Distance Education, knowing its operation and coming to understand it. In this way, we sought to investigate several aspects of the teaching and learning process of the Distance Education Teaching students of the Federal Rural Semiarid University and from these aspects, some contributions were suggested to maximize this method of teaching. To carry out this research, the qualitative approach was used, and the data collection technique used was the semi structured interview conducted with the students of the University's Distance Education Center. Based on the analysis of the results, it was observed that Distance Education was adopted by students who are looking for an undergraduate course to better qualify for the job market, since they usually work or already have another training, and due to the unavailability of Time, or long distances cannot attend assiduously attending classes
Monografia
Keywords: Educação a distância; Ensino; Qualificação profissional; Distance education; Teaching; Professional qualification; CIENCIAS SOCIAIS APLICADAS::ADMINISTRACAO